(untitled) (Journal of humanities and social sciences exploratio, 2026)
’buddy Culture’ is a light form of social interaction characterized by its transience, functionality, and low burden, which has gained popularity among Generation Z youth. This article argues that the main reasons why ’finding a partner’ as a social behavior is popular among young people are threefold: first, young people leave familiar environments due to studying or working, causing changes in their stable social circles; second, interest-based social groups are gradually replacing traditional geographic or familial relationships, allowing youth to freely join different interest-based communities; third, the development of social media has provided an opportunity for ’partner culture.’ At the same time, partner-based socializing has both positive and negative effects. On the one hand, its precise and vertical matching approach can quickly connect individuals with companions who meet specific needs, reducing social pressure while expanding social networks. On the other hand, transient social interactions can lead to a lack of deep emotional connections. Seeking partners for specific goals can, to some extent, lead to alienation, and finding partners online also carries certain risks. Finally, this article offers strategic suggestions for youth partner socializing from three levels: individual, platform, and society.